Why US Trade Deficit with China is not too bad after all - Lim, Thow Wee (2009)
Is the U.S. trade deficit made in China? The short answer is no. In recent years U.S. bilateral trade deficits have been increasing not only with China but most other trading partners as well. The imbalance on bilateral trade with China, though large, still accounts for less than one-quarter of the total. However, official purchases of U.S. dollar assets by China and other U.S. trading partners have facilitated the continued high level of U.S. domestic spending, and some analysts believe that large foreign purchases of U.S. assets have been responsible for keeping U.S. long-term interest rates low.